Autophagy in the pathogenesis and therapeutic potential of post-traumatic osteoarthritis. Issue 1 (31st January 2023) - Gong, Yunquan; Li, Song; Wu, Jinghui; Zhang, Tongyi; Fang, Shunzheng; Feng, Daibo; Luo, Xiaoqing; Yuan, Jing; Wu, Yaran; Yan, Xiaojing; Zhang, Yan; Zhu, Jun; et al.
Abstract: Autophagy, as a fundamental mechanism for cellular homeostasis, is generally involved in the occurrence and progression of various diseases. Osteoarthritis (OA) is the most common musculoskeletal disease that often leads to pain, disability and economic loss in patients. Post-traumatic OA (PTOA) is a subtype of OA, accounting for >12% of the overall burden of OA. PTOA is often caused by joint injuries including anterior cruciate ligament rupture, meniscus tear and intra-articular fracture. Although a variety of methods have been developed to treat acute joint injury, the current measures have limited success in effectively reducing the incidence and delaying the progression of PTOA. Therefore, the pathogenesis and intervention strategy of PTOA need further study. In the past decade, the roles and mechanisms of autophagy in PTOA have aroused great interest in the field. It was revealed that autophagy could maintain the homeostasis of chondrocytes, reduce joint inflammatory level, prevent chondrocyte death and matrix degradation, which accordingly improved joint symptoms and delayed the progression of PTOA. Moreover, many strategies that target PTOA have been revealed to promote autophagy. In this review,   we summarize the roles and mechanisms of autophagy in PTOA and the current strategies for PTOA treatment that depend on autophagy regulation, which may be beneficial for PTOA patients in the future.